TRAINED IN THE NEW NORMAL: HOW CONFIDENT ARE PRE-SERVICE TEACHERS? - LYNN MICHELLE L. GOROSPE , MYRJE J. PATRICIO, MAED (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The self-efficacy beliefs of pre-service teachers can be used as a predictor of their capacity to handle the task in their teaching immersion. As many studies show that high teacher self-efficacy means high effectiveness in handling classroom obligations and challenges. This study aimed to investigate the relationship of individual innovativeness and personal values to the self-efficacy of pre-service teachers who underwent blended learning modality during their Field Studies and teaching immersion. Spearman rank correlation was used to determine the relationship. It was found out that their self-efficacy, individual innovativeness and personal values are of excellent level based on their respective net agreement ratings. Spearman analysis showed that personal values and individual innovativeness have strong direct proportional relationships to their self-efficacy. The respondents of the study, though, trained in a blended platform, have high teacher self-efficacy as related to their high personal values and individual innovativeness. With this the researchers recommend that teacher education programs may incorporate training and activities that focus on the improvement of personal values and individual innovativeness to foster greater confidence in their professional capabilities.